Comparing the Trajectory of Urban Impervious Surface in Two Cities: The Case of Accra and Kumasi, Ghana - Thomas Mumuni Bilintoh; Andrews Korah; Antwi Opuni; Adeline Akansobe (Land, 2023)
In this study, we present methods to assess newly developed urban impervious surface (UIS) datasets derived from satellite imagery of the cities of Kumasi and Accra, Ghana, at three different time points. Each city has three binary maps from 2000, 2011, and 2021, in which one shows the presence of UIS and zero shows its absence. We employed the binaryTimeSeries method to compare the gross gains and losses in the two cities. In addition, we show how three components of change—quantity, allocation, and alternation—compare across the two sites. The results show that both cities experienced a large proportion of gains during the change in impervious surfaces between 2000 and 2011, and 2011 and 2021, with relatively smaller loss proportions and alternations. Comparatively, the results from the components of change show that change is fastest in Kumasi, which had a larger proportion of quantity gain. Our methods show an acceleration in UIS in the two cities during the temporal extent, and this trend is likely to continue with increasing urban populations. As a result, we recommend that the Land Use and Spatial Planning Authority, Town and Country Planning and other stakeholders make contingency plans to regulate the unplanned increase in UIS, since other studies have shown their negative effects on people and the environment.